2016
DOI: 10.1002/lary.26312
|View full text |Cite
|
Sign up to set email alerts
|

Auditory brainstem implant program development

Abstract: We suggest sets of criteria necessary for the development of successful and sustaining ABI programs, including programs for NF2 patients, postlingually deafened adult nonneurofibromatosis type 2 patients, and congenitally deaf pediatric patients. Laryngoscope, 127:1909-1915, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Only a few patients achieved open-set speech perception through ABI audition alone. These results have not greatly changed throughout the past 20 years (Schwartz et al 2008;Matthies et al 2014;Schwartz & Wilkinson 2017). Thus, most ABI patients still rely on a combination of speechreading, writing, and sign language to communicate.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few patients achieved open-set speech perception through ABI audition alone. These results have not greatly changed throughout the past 20 years (Schwartz et al 2008;Matthies et al 2014;Schwartz & Wilkinson 2017). Thus, most ABI patients still rely on a combination of speechreading, writing, and sign language to communicate.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, Colletti and Shannon reported that ABI can be applied to adults and children with non-NF2 hearing loss who would not benefit from CI surgery [13]. However, the use of ABI in these patient groups is not FDA approved [14]. Although the results are not completely clear, it is known that ABI has been applied to approximately 1000 patients to date.…”
Section: Journal Of Bionic Memorymentioning
confidence: 99%
“…The practical significance of the electrophysiological study of the human auditory midbrain lies in auditory midbrain implants [23,63]. Auditory brainstem implant (ABI) is an electronic device indicated for use when anatomic or functional characteristics do not allow to use of cochlear implant or other hearing technologies, such as fully implantable hearing aids and hearing aids for sound amplification.…”
Section: Introductionmentioning
confidence: 99%